Direct oral anticoagulants decrease treatment failure for acute lower extremity deep venous thrombosis. (December 2022) - Hekman, Katherine E; Chao, Calvin L; Morgan, Courtney E; Helenowski, Irene B; Eskandari, Mark K
Objective: Optimal medical therapy for acute lower extremity deep venous thrombosis (DVT) remains an enigma. While clinical trials demonstrate non-inferiority with an oral anti-Xa inhibitor, or direct oral anticoagulant (DOAC), versus combined low–molecular weight heparin (LMWH) and oral vitamin K antagonist (VKA), the most effective regimen remains to be determined. Methods: This study is a single-center retrospective cohort study from October 2014 to December 2015 of patients with a diagnosis of acute DVT and subsequent serial lower extremity venous duplex. Demographics, medical history, medications, serial ultrasound findings, as well as the primary anticoagulant used for treatment were collected and analyzed by two independent data extractors. Treatment failure was defined as any new DVT or progression of an existing DVT within 3 months of diagnosis of the index clot. Risk factors for treatment failure were assessed using standard odds ratios and Fischer's exact test. Results: Among 496 patients with an acute lower extremity DVT, 54% ( n = 266) were men, mean age was 61 years, 35% ( n = 174) involved the popliteal or more proximal segments, and 442 had documentation of the primary treatment for DVT: 20% ( n = 90) received nothing; 20% ( n = 92) received an oral VKA; 34% ( n = 149) received a DOAC; 20% ( n = 90) received LMWH; and 5% ( n = 21) received another class of anticoagulant. Within 3 months, 21% ( n =89 out of 427) had treatment failure defined as any new DVT or progression of prior DVT. Patients treated with a DOAC were less likely to experience treatment failure when compared with any other treatment (odds ratio 0.43; 95% confidence intervals [0.23, 0.79]; p = 0.0069) and when compared with traditional oral VKA (OR 0.44; 95% CI [0.21, 0.92]; p = 0.029). None of prior history of DVT, pulmonary embolism, thrombophilia, renal insufficiency, hepatic insufficiency, cancer, or antiplatelet therapy correlated with treatment failure. Treatment outcome did not correlate with being on any anticoagulation versus none ( p = 0.74), nor did it correlate with the duration of treatment (<3 months versus ≥3 months) ( p = 0.42). Proximal and distal DVTs showed no difference in treatment failure (19% versus 22%, respectively; p = 0.43). Conclusion: In summary, the use of a DOAC for acute lower extremity DVT yielded better overall outcomes and fewer treatment failures at 3 months as compared to traditional oral VKA therapy based on serial duplex imaging.